2015
DOI: 10.3382/ps/pev194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary probiotic and high stocking density on the performance, carcass yield, gut microflora, and stress indicators of broilers

Abstract: A study was carried out to evaluate the effect of dietary probiotic supplementation and stocking density on the performance, relative carcass yield, gut microflora, and stress markers of broilers. One-day-old Ross 308 male broiler chickens (n = 480) were allocated to 4 experimental groups for 42 d. Each treatment had 8 replicates of 15 chicks each. Two groups were subjected to a high stocking density (HSD) of 20 birds/m² and the other 2 groups were kept at low stocking density (LSD) of 10 birds/m². A basal die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
5
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 45 publications
8
87
5
3
Order By: Relevance
“…Consistent with our results, Thaxton et al (2006) and Chegini, Kiani, and Rokni (2018) observed that NO concentration was increased by the high stocking densities. In contrast with our findings, Cengiz et al (2015) found that the blood NO of broilers was not affected by the stocking density. In contrast with our findings, Cengiz et al (2015) found that the blood NO of broilers was not affected by the stocking density.…”
Section: Effect Of High Stocking Density On Plasma Mda and No Levelscontrasting
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, Thaxton et al (2006) and Chegini, Kiani, and Rokni (2018) observed that NO concentration was increased by the high stocking densities. In contrast with our findings, Cengiz et al (2015) found that the blood NO of broilers was not affected by the stocking density. In contrast with our findings, Cengiz et al (2015) found that the blood NO of broilers was not affected by the stocking density.…”
Section: Effect Of High Stocking Density On Plasma Mda and No Levelscontrasting
confidence: 99%
“…Furthermore, it was reported that environmental stress, including high temperature, causes oxidative stress with increased production of MDA (Halliwell & Gutteridge, 1984). On the contrary, Cengiz et al (2015) reported that the blood MDA of broilers was not affected by the stocking density. These different outcomes could be due to the various stress condition of birds such as severity of stressful condition and type of stress.…”
Section: Effect Of High Stocking Density On Plasma Mda and No Levelsmentioning
confidence: 99%
“…In this regards, Mountzouris et al () reported that dietary probiotics improved BWG and FCR in broilers by secretion of different digestive enzymes (amylolytic, proteolytic and lipolytic) in the intestines. However, Cengiz et al () showed that there was no interaction between dietary probiotic and stocking density in broilers. Vargas‐Rodr´iguez et al () reported that FI, BWG or FCR were not affected by supplementation of broiler diet with probiotic throughout the growing period.…”
Section: Discussionmentioning
confidence: 99%
“…Chick placement [1,[17][18][19][20][21][22] Increased stocking density [23][24][25][26][27][28][29][30][31] Weighing, grading, group formation, catching, transferring to breeder houses [1,18,19] Prolonged egg storage, egg transportation, inadequate egg storage conditions, incorrect incubation regimes [1,18,19] Environmental stressors…”
Section: Technological Stressorsmentioning
confidence: 99%